Quo Vadis, Belis Masyarakat Sikka Maumere - Yosef Dentis (Ekspektasi: Jurnal Pendidikan Ekonomi, 2020)
Talking about the belis, which is studied from the word alone, it means that belis is a dowry with the size of payment, and usually depends on bargaining. Adat or lasim are called rules that have existed and been carried out since time immemorial in ways and customs which are used as a from of cultural ideas which consist of cultural values, norms, laws and rules which are related to one another into one system. The study of thoughts about Quoa Vadis Belis brings us to one thing that deserves a deeper study where you or we go and find out what belis means according to Sikka Maumere. The main problem examined in this study is how to calculate Belis and how it impacts society in changing the life of socio-cultural economy. The objectives of this research are; first to know the concept of belis, second; integrity and economics, third is how the perspective of the older and younger generations in placing belis in the Sikka Maumere community. The method used in this research descriptive qualitative research. Techniques and data analysis are data reduction, data presentation and conclusion. The result of the research show that belis in the Sikka Maumere community is not only entrenched but also an integral part or all the parts that need to be a complete and perfect complement to a socio-economic and cultural approach pattern.